Teach yourself visually HTML5 - Wooldridge, Mike (Teach yourself visually., 2011)
"Are you a visual learner? Do you prefer instructions that show you how to do something and skip the long-winded explanations? If so, then this book is for you. Open it up and you'll find clear, step-by-step screen shots that show you how to tackle more than 165 HTML5 tasks. Each task-based spread covers a single technique, sure to help you get up and running on HTML5 in no time"--Publisher's description.